2022
DOI: 10.4028/p-db512a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr Concentration on the Microstructure and Mechanical Performance of Porous Ti-Zr System by Powder Metallurgy

Abstract: In this study, porous binary Ti-(x)Zr alloys of nominal Zr contents (x=10, 20 and 30 at. %) with differing porosities were manufactured, using powder metallurgy with compaction conducted under a pressure of 300MPa and sintering at 1200 °C for 6 h. A space holder agent was employed to control the general porosity. The microstructures were characterized by scanning electron microscopy and energy dispersed spectroscopy. The phase constitution was done by X-ray diffractometer. Uniaxial compressive tests were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, it can be observed that the micrograph of the Ti-15Zr alloy has finer lamellae structure of grains compared to the CP-Ti sample. Consequently, increasing Zr concentration led to refine the grains; the microstructure of Ti-Zr system was extremely sensitive to Zr content (Eyyup et al, 2022). Also, for Ti-15Zr…”
Section: Resultsmentioning
confidence: 99%
“…However, it can be observed that the micrograph of the Ti-15Zr alloy has finer lamellae structure of grains compared to the CP-Ti sample. Consequently, increasing Zr concentration led to refine the grains; the microstructure of Ti-Zr system was extremely sensitive to Zr content (Eyyup et al, 2022). Also, for Ti-15Zr…”
Section: Resultsmentioning
confidence: 99%